EFEKTIFITAS SENAM HAMIL TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER 2 DAN 3 DI DESA MARGALUYU WILAYAH KERJA PUSKESMAS KASEMEN - Nila Marwiyah; Pratiwi Anjar Sari (Jurnal Kesehatan, 2017)
Pregnancy exercise is a suggested movement for pregnant women to prepare physically, and mentally pregnant women during pregnancy and improve the health of pregnant women. Pregnancy disorder that usually happened is pregnant women with high level of anxiety of trimester 2 and 3. The purpose of this study to determine the effect of pregnancy exercise on the level of anxiety of pregnant women trimester 2 and 3 in the Village Margaluyu Work Area Puskesmas Kasemen Year 2017. Type of research using quasi experiment pre post without control design. The sample that used by 14 pregnant women were taken using total sampling. Instruments that used was Perinatal Anxiety Screening Scale (PASS). Result of the t test of dependent obtained significant value is p = 0.000. The conclusions show that there is an effect of anxiety levels before and after pregnancy exercise. The advice for health workers can provide motivation to pregnant women about the importance of pregnancy exercise for the health of pregnant women.